Artificial Intelligence and Extended Reality for Interactive Museum Experiences: Designing Participatory, Multisensory, and Adaptive Spaces for Knowledge Sharing - Salvetti, Fernando; Bertagni, Barbara (International Journal of Advanced Corporate Learning (iJAC), 2026)
Museums, archives, and cultural institutions are experiencing a profound transformation, shifting from repositories of exclusive knowledge to interactive and inclusive environments that foster lifelong learning and cultural participation. Building on the historical evolution of collections—from ancient archives and Renaissance Wunderkammern to modern public museums—this paper explores how extended reality (XR), AI-driven avatars, and digital storytelling are reshaping the visitor experience. We analyze how immersive projections, conversational agents, and hybrid “phygital” installations developed by e-REAL Labs have enhanced accessibility, engagement, and preservation across projects in Italy, Switzerland, France, and beyond. These solutions demonstrate how static exhibitions can be converted into dynamic experiences where visitors actively co-construct meaning. Drawing on recent design research, we highlight the importance of cognitive ergonomics, memory, and attention management in XR environments, ensuring that technology supports rather than overwhelms perception. The integration of calm and slow technologies provides balance, making digital tools discreet companions to narrative and curatorial intent. Similarly, modular and adaptive design principles allow installations to fit within diverse architectural and cultural contexts without fragmenting visitor experience. Particular focus is placed on the educational dimension of interactive museums., where extended reality (XR) and artificial intelligence (AI) extend learning beyond traditional didactics, This approach engages visitors through multisensory experiences that blend physical artifacts with virtual reconstructions. Multilingual avatars and inclusive design guidelines support accessibility for diverse audiences, including individuals with disabilities and marginalized communities. Ultimately, this paper positions interactive museum experiences as a new paradigm of cultural engagement, where digital transformation does not replace authenticity but enhances it. By merging historical preservation with generative AI and immersive storytelling, museums can transcend physical and cognitive barriers, offering equitable access to cultural heritage and fostering dialogue across generations and cultures.